BIOENSAIOS APLICADOS A ESTUDOS DE ATIVIDADE BACTERICIDA EM COMPLEXO METÁLICO CONTENDO AG(I) E SEU LIGANTE NATURAL - CABRAL JÚNIOR, B. P.; CABEZA, N. A.; BISCOLI, L. O.; TEIXEIRA, E. I.; FAGANELLO, N. L.; ANJOS, A. (ANAIS DO ENIC, 2016)
-